Peran Kompetensi SDM, Dan Partisipasi Masyarakat Terhadap Kinerja Pelayanan Publik Kecamatan Sampang Kabupaten Sampang Yang Dimediasi Oleh Profesionalisme - Mat Latip; Hadi Susanto; Sri Mulyani (Journal of Management and Creative Business, 2023)
Mat Latip, 2023. The Role of HR Competence, and Community Participation in the Performance of Public Services in Sampang District, Sampang Regency Mediated by Professionalism, Wijaya Putra University Postgraduate Program. This type of researchis explanatory, namely explaining causal relationships between variables to test hypotheses. By using a quantitative approach, the research sample was 86 respondents. Inthis study the data will be processed using SEM-PLS data analysis. The aims of this research are: 1). To describe the competence of human resources, community participation, professionalism and performance of public services. 2) To test and analyze HR competencies that have a significant influence on the performance of public services. 3) To test and analyze HR competencies that have a significant influence on professionalism. 4) To test and analyze community participation has a significant influence on the performance of public services. 5) To test and analyze community participation has a significant influence on professionalism. 6) To test and analyze professionalism has a significant influence on the performance of public services. 7) To test and analyze HR competencies that have a significant influence on the performance of public services mediated by professionalism. 8) To test and analyze community participation has a significant influence on the performance of public services mediated by professionalism. The research results show that: 1). HR competence has a significant effect on the performance of public services in Sampang District, Sampang Regency. 2) HR competence has a significant effect on professionalism in Sampang District, Sampang Regency. 3) Community participation has a significant effect on the performance of public services in Sampang District, Sampang Regency. 4) Community participation has a significant effect on professionalism in Sampang District, Sampang Regency. 5) Professionalism has a significant effect on the performance of public services in Sampang District, Sampang Regency. 6) HR competence has no significant effect on the performance of public services in Sampang District, Sampang Regency which is mediated by professionalism. 7) Community participation has a significant effect on the performance of public services in Sampang District, Sampang Regency which is mediated by professionalism.